HUBUNGAN KETEPATAN PEMBERIAN MP-ASI TERHADAP STATUS GIZI BAYI USIA 0-12 BULAN DI DESA KALIWINING KECAMATAN RAMBIPUJI KABUPATEN JEMBER - Kustin Kustin (LPPM Universitas dr. Soebandi, 2013)
Breast milk supplement is food besides breast feeding for babies at 6 months years old or more (Sunaryo, 2008). When the age of the babies increase, the baby’s need for nutritions food also increases. The introduction and giving of the supplement should be suited with the age, ability to digest and to receive food and be also given gradually in term of texture, consistency, portion and frequency. According to data taken from monthly nutrition report at Pustu Kaliwining and Puskesmas Rambipuji, we know that 80 % babies get breast feeding supplement early and 6,4 % experiencing bad nutrition. This research was made in order to analysis the accuracy relation about giving food besides breast feeding and the nutrition status of the babies. This study was an analytic where the data were obtained through a cross sectional design and the population was 186 persons. The sample was 127 babies and their mothers. It was taken using a proporsional stratified random sampling and with Chi Square analysis. The results showed that the breast feeding supplement was given correctly (36 %) and incorrectly (64 %). And from the criteria of the nutrition status on the bais of body’s weight (Health Care Record), it was shown that there were 68 % babies with good nutrition status, 9 % with bad nutrition status and 23 % inadequate nutrition status. Based on the statistical test of Chi Square using SPSS For Windows, it is known that there is a conclusion between the accuracy in giving breast feeding supplement and the nutrition status of the babies in 0-12 months years old as shown by p cost is lower than α cost 0,05. It is suggested that midwives have to more active in order to give information about the importance giving breast feeding supplement exactly to mothers in the various meeting.